2019
DOI: 10.1116/1.5125109
|View full text |Cite
|
Sign up to set email alerts
|

Thermal atomic layer deposition of ruthenium metal thin films using nonoxidative coreactants

Abstract: Atomic layer deposition (ALD) of ruthenium metal films is presented using (η4-2,3-dimethylbutadiene)(tricarbonyl)ruthenium [Ru(DMBD)(CO)3] with the coreactants 1,1-dimethylhydrazine, hydrazine, or tert-butylamine. The dependence of growth rate on precursor pulse lengths at 200 °C showed a saturative, self-limited behavior at ≥3.0 s for Ru(DMBD)(CO)3 and ≥0.1 s for 1,1-dimethylhydrazine. An ALD window was observed from 200 to 210 °C, with a growth rate of 0.42 Å/cycle. Films grown at 200 °C showed rms surface r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…The surface metal oxides are unstable and decompose to give metals at elevated temperatures. 12 For thermal ALD of Ru using dimethylbutadiene-based precursor Ru(DMBD)(CO)3 and non-oxidative reactants hydrazine, the achieved growth rate is 0.42 Å /cycle with an ALD temperature window from 200 °C to 210 °C. 12 In addition to thermal ALD, plasma-enhanced ALD (PE-ALD) has been used with ammonia or a mixture of N2 and H2 as the N-plasma source.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The surface metal oxides are unstable and decompose to give metals at elevated temperatures. 12 For thermal ALD of Ru using dimethylbutadiene-based precursor Ru(DMBD)(CO)3 and non-oxidative reactants hydrazine, the achieved growth rate is 0.42 Å /cycle with an ALD temperature window from 200 °C to 210 °C. 12 In addition to thermal ALD, plasma-enhanced ALD (PE-ALD) has been used with ammonia or a mixture of N2 and H2 as the N-plasma source.…”
mentioning
confidence: 99%
“…12 For thermal ALD of Ru using dimethylbutadiene-based precursor Ru(DMBD)(CO)3 and non-oxidative reactants hydrazine, the achieved growth rate is 0.42 Å /cycle with an ALD temperature window from 200 °C to 210 °C. 12 In addition to thermal ALD, plasma-enhanced ALD (PE-ALD) has been used with ammonia or a mixture of N2 and H2 as the N-plasma source. [13][14][15] For the PE-ALD of Ru using RuCp2 and NH3 plasma at a temperature of 300 °C, a growth rate of 1.2 Å/cycle has been reported, while a growth rate of 1.8 Å/cycle was reported using Ru(EtCp)2 at 300 °C.…”
mentioning
confidence: 99%
“…The authors reported a constant GPC of 0.8 Å/cycle at 260-280 °C, with a decrease or increase in GPC with increasing temperature at temperatures above or below the 260-280 °C range, respectively. Cwik et al [43] reported a constant GPC of 0.4 Å/cycle at 200-210 °C and a steadily increasing GPC with increasing temperature both above and below the 200-210 °C range. The counter-reactant in that study was 1,1-dimethylhydrazine.…”
Section: Introductionmentioning
confidence: 99%
“…and (iii) what is the general expected relationship between GPC and temperature for a zero-oxidation state precursor?Recently, several studies have reported the ALD of high-quality Ru films from η 4 -2,3dimethylbutadiene ruthenium tricarbonyl [Ru(DMBD)(CO)3(0)], using either O2 [34,45,48] or various non-oxidative counter-reactants such as H2O or hydrazine. [43,44,49] The studies indicate that this precursor is an exceptional candidate for Ru vapor deposition, as it is volatile and thermally stable, does not suffer from a nucleation delay on SiO2, and yields pure and smooth Ru films at relatively low temperatures. Yet, a closer look at the reported GPC as a function of temperature and counter-reactant in the earlier reports reveals significant discrepancies.…”
mentioning
confidence: 99%